Synthesis method of ethylene glycol condensation crosslinking acrylic resin

By synthesizing and processing polystyrene white spheres, condensation crosslinking resins with ester groups and high hydrophilicity are formed, which solves the problem of poor effect of existing resins when adsorbing indodyl sulfate and p-cresol sulfate, and achieves more efficient adsorption performance and biocompatibility.

CN119529162APending Publication Date: 2025-02-28HEBEI LIJIANG BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411714594.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing adsorbent resins are not effective when adsorbing macromolecular toxins such as indodol sulfate and p-cresol sulfate, and are not hydrophilic, which affects biocompatibility.

Method used

By synthesizing polystyrene white spheres containing ester groups of a certain pore size, acidic hydrolysis and ethylene glycol condensation crosslinking reactions are carried out to obtain a condensation crosslinking macroporous resin containing ester groups. The resin forms carboxy and hydroxyl groups under acidic conditions, improves hydrophilicity and specific surface area, and enhances adsorption performance.

Benefits of technology

The adsorption properties of resins to indoxyl sulfate and to cresol sulfate are significantly improved, and biocompatibility is improved through hydroxyl groups to provide a stronger adsorption site.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005156616220000041
    Figure BDA0005156616220000041
  • Figure BDA0005156616220000042
    Figure BDA0005156616220000042
  • Figure BDA0005156616220000043
    Figure BDA0005156616220000043
Patent Text Reader

Abstract

The invention discloses a synthesis method of ethylene glycol condensation crosslinking acrylic resin, and belongs to the technical field of adsorption resin for blood perfusion. Comprising the following steps: preparing a water phase, preparing an oil phase, polymerizing, carrying out acidic hydrolysis and carrying out ethylene glycol condensation crosslinking, namely drying the carboxyl-containing resin obtained in the previous step, adding into a reactor, and adding ethylene glycol into the reactor for full swelling. The preparation method comprises the following steps: synthesizing ester group-containing polystyrene white balls with a certain aperture, hydrolyzing resin under an acidic condition, soaking the resin in an acid solution, washing the resin to obtain macroporous resin containing a certain carboxyl group, and carrying out an ethylene glycol condensation crosslinking reaction on the carboxyl group to obtain ester group-containing condensation crosslinked macroporous resin. The adsorbent can be applied to the adsorption of indoxyl sulfate and p-cresol sulfate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical adsorption resins, and in particular relates to a macroporous adsorption resin containing hydroxyl groups. Background Art

[0002] Hemoperfusion is a blood purification technology that introduces the patient's blood into a perfusion device filled with solid adsorbents to remove exogenous or endogenous toxins, drugs or metabolic wastes in the blood that cannot be removed by dialysis through adsorption. It is mainly used to rescue drug and poison poisoning, and can also be used in combination with hemodialysis to remove large molecular toxins in patients with chronic renal failure who are undergoing maintenance dialysis.

[0003] One of the adsorbents is resin. Adsorption resin is a kind of artificially synthesized organic polymer with macroporous structure. Because of its porous structure and screening property, it has adsorption through surface adsorption, surface electrical properties or hydrogen bond formation. Resin generally adsorbs medium molecules. At present, it is mainly neutral macroporous adsorption resin, and the adsorption capacity is directly related to the characteristics of the resin molecular group. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a method for synthesizing an ethylene glycol condensation cross-linked acrylic resin. The method comprises the following steps: synthesizing polystyrene white balls containing ester groups with a certain pore size, firstly hydrolyzing the resin under acidic conditions, soaking and washing with acid solution to obtain a macroporous resin containing a certain number of carboxyl groups, and then subjecting the carboxyl groups to an ethylene glycol condensation cross-linking reaction to obtain a condensation cross-linked macroporous resin containing an ester group, which can be used for the adsorption of indoxyl sulfate and p-cresol sulfate.

[0005] The synthesis method comprises the following steps:

[0006] (1) preparing an aqueous phase: adding water, gelatin, polyvinyl alcohol, magnesium sulfate, sodium carbonate and methylene blue into a reaction vessel, heating and stirring until the gelatin and polyvinyl alcohol are completely dissolved, and then continuing to stir for half an hour as the aqueous phase;

[0007] (2) preparing an oil phase: adding divinylbenzene, methyl methacrylate, styrene, toluene, isobutyl alcohol, BPO and azobisisobutyronitrile into a reaction vessel and mixing them evenly as the oil phase;

[0008] (3) Polymerization: slowly add the oil phase to the water phase, control the speed of stirring at 120 r / min until the stirring is constant, continue to stir at a constant speed for 10 minutes, heat up to 78°C at a rate of 5°C / 15min, continue to heat up to 85°C at a rate of 5°C / 10min after the resin is fixed for 3 hours, keep it warm for 2 hours, continue to heat up to 95°C at a rate of 5°C / 10min, keep it warm for 6 hours and then take it out; wash the polyvinyl alcohol on the surface of the resin with warm water, extract the porogens toluene and isobutyl alcohol with acetone using a Soxhlet extractor, wash with water and dry to obtain a white ball resin;

[0009] (4) Acid hydrolysis: Add the white ball resin to a reactor, add a 5% sulfuric acid solution to the reactor to cover the resin, stir to allow the sulfuric acid to fully enter the resin, stir for about 2 hours, and heat to 90-95°C at a rate of 5°C / 10min to hydrolyze; after the hydrolysis is completed, soak with a 10% sulfuric acid solution to dissolve the organic and inorganic substances in the resin, soak for about 2 hours, and wash off the excess sulfuric acid with pure water to obtain a resin containing carboxyl groups;

[0010] (5) Ethylene glycol condensation crosslinking: The carboxyl resin obtained in the previous step is dried and added to the reactor. Ethylene glycol is added to the reactor to fully swell the resin. During the swelling process, the temperature in the reactor is controlled not to exceed 15°C. After the swelling is completed, 0.5% sulfuric acid solution is added dropwise and mixed evenly to make the pH of the system less than 1. The temperature is raised to 75°C for full reaction.

[0011] In the aqueous phase, add 10-15 g gelatin, 16-20 g polyvinyl alcohol, 16-20 g magnesium sulfate, 55-58 g sodium carbonate, and 6-7 drops of methylene blue per liter of water.

[0012] The mass ratio of divinylbenzene, methyl methacrylate, styrene, toluene, isobutyl alcohol, BPO and azobisisobutyronitrile in the oil phase is 8-10:80-120:85-95:70-90:300-400:1-2:1.

[0013] In step (3), the mass ratio of the water phase to the oil phase is 2-4:1.

[0014] In step (5), 4-6 g of ethylene glycol is added per gram of resin containing hydroxyl groups.

[0015] The preferred aqueous phase comprises 12.5 g of gelatin, 18.75 g of polyvinyl alcohol, 18.75 g of magnesium sulfate and 56.25 g of sodium carbonate per liter of water.

[0016] The preferred mass ratio of divinylbenzene, methyl methacrylate, styrene, toluene, isobutyl alcohol, BPO and azobisisobutyronitrile in the oil phase is 9:100:91:80:320:1.4:1.

[0017] The invention also provides application of the prepared resin in adsorbing indoxyl sulfate and p-cresol sulfate.

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] By synthesizing polystyrene white balls with a certain pore size and containing ester groups, the resin is first hydrolyzed under acidic conditions, and then soaked and washed with acid (either sulfuric acid or hydrochloric acid) to obtain a macroporous resin containing a certain number of carboxyl groups. The carboxyl groups are then subjected to ethylene glycol condensation cross-linking reaction to obtain a condensation cross-linked macroporous resin containing ester groups, which has good adsorption performance for indoxyl sulfate and p-cresol sulfate.

[0020] A cross-linking agent containing an ester group is selected, which produces carboxyl and hydroxyl groups after hydrolysis. The hydroxyl group can increase the hydrophilicity of the resin and thus improve the biocompatibility. The carboxyl group is mainly used for cross-linking reaction with ethylene glycol, which can greatly increase the specific surface area and provide more adsorption sites for adsorbed substances. At the same time, the ester group produced by cross-linking has a medium-grade property and can combine more firmly with the adsorbed substance. DETAILED DESCRIPTION

[0021] The present invention is further described below by means of specific examples. However, those skilled in the art should be aware that the specific examples of the present invention do not limit the present invention in any way, and any equivalent replacements made on the basis of the present invention fall within the protection scope of the present invention.

[0022] Example 1

[0023] (1) Preparation of aqueous phase: Add 800 ml of water to a 2000 ml three-necked flask and heat to 45°C. Add 10 g of gelatin, 15 g of polyvinyl alcohol, 15 g of magnesium sulfate, 45 g of sodium carbonate, and 5 drops of methylene blue. Stir for 20 min until gelatin and polyvinyl alcohol are completely dissolved. Stir for half an hour as the aqueous phase.

[0024] (2) Preparation of oil phase: Add 4.5 g of divinylbenzene (95%), 50 g of methyl methacrylate, 45.5 g of styrene, 40 g of toluene, 160 g of isobutyl alcohol, 0.7 g of BPO and 0.5 g of azo into a beaker and stir evenly. If necessary, ultrasonically mix to obtain the oil phase.

[0025] (3) Polymerization: Slowly add the oil phase to the water phase, start stirring and control the speed to 120r / min until the stirring is constant, and stir at a constant speed for 10 minutes. Raise the temperature from 45°C to 78°C at a rate of 5°C / 15min. After the resin is fixed for 3 hours, continue to raise the temperature to 85°C at a rate of 5°C / 10min, keep it warm for 2 hours, continue to raise the temperature from 85°C to 95°C at a rate of 5°C / 10min, keep it warm for 6 hours and then take it out. Wash the polyvinyl alcohol on the surface of the resin with warm water, extract the porogen with acetone in a Soxhlet extractor for 8 hours, wash with water and dry it to obtain white ball resin.

[0026] White ball indicators:

[0027]

[0028] (4) Acidic hydrolysis: Take 20g of dry white ball resin, add 100ml of purified water into a three-necked flask, add 50g of 5% sulfuric acid solution, stir for 2h, heat to 90-95℃ at a rate of 5℃ / 10min for hydrolysis, soak in 10% sulfuric acid solution for 2h, and wash with purified water for 1h. (At this time, the ester group in the resin forms a carboxyl group under the condition of sulfuric acid solution. A resin containing carboxyl groups is obtained).

[0029] Resin index:

[0030]

[0031] (5) Ethylene glycol condensation crosslinking: 20g of the dried resin after hydrolysis was added to a three-necked flask, and 100g of ethylene glycol was added to swell for 3h. During the swelling process, the temperature in the autoclave was controlled not to exceed 15°C. After the swelling was completed, 0.5% sulfuric acid solution was added dropwise and mixed evenly to make the pH value of the system <1, and then the temperature was raised to 75°C for reaction for 12h.

[0032] Condensation cross-linking resin indicators:

[0033]

[0034] Adsorption performance test:

[0035] 1. Adsorption performance of indoxyl sulfate

[0036] Prepare an aqueous solution of indoxyl sulfate at a concentration of 25 mg / L, take 25 mL and place it in a 50 mL stoppered conical flask, weigh 1.0 g of the resin adsorbent prepared in Example 1 (dry weight, the wet state can be converted into dry weight or directly weigh the adsorbent after constant weight by atmospheric pressure drying method) and put it into the flask, place it in a reciprocating constant temperature water bath oscillator at (37±1)°C and oscillate at a rate of (60±10) times / min for 2 h, measure and calculate the concentration of indoxyl sulfate solution before and after adsorption by ultraviolet spectrophotometry at 216 nm, and calculate the decline rate according to formula (1):

[0037]

[0038] Where:

[0039] c r1 ——Decrease rate of indoxyl sulfate solution, %;

[0040] c 01 ——Concentration of indoxyl sulfate solution before adsorption, in milligrams per liter (mg / L);

[0041] c t1 ——Concentration of indoxyl sulfate solution after 2 hours of adsorption, in milligrams per liter (mg / L);

[0042] 2. Adsorption performance of p-cresol sulfate

[0043] Prepare a 25 mg / L aqueous solution of p-cresol sulfate, take 25 mL and place it in a 50 mL conical flask with a stopper, weigh 1.0 g of adsorbent (dry weight, wet state can be converted to dry weight or directly weigh the adsorbent after constant weight by atmospheric pressure drying method) and put it into the flask, place it in a reciprocating constant temperature water bath oscillator at (37±1)℃ and oscillate at a rate of (60±10) times / min for 2 hours, measure and calculate the concentration of p-cresol sulfate solution before and after adsorption by ultraviolet spectrophotometry at 210 nm, and calculate the decline rate according to formula (2):

[0044]

[0045] Where:

[0046] c r2 ——Decrease rate of sulfuric acid p-cresol solution, %;

[0047] c 02 ——Concentration of p-cresol sulfate solution before adsorption, in milligrams per liter (mg / L);

[0048] c t2 ——Concentration of p-cresol sulfate solution after 2 hours of adsorption, in milligrams per liter (mg / L); 3. Adsorption performance for creatinine

[0049] Prepare a 35 mg / L creatinine aqueous solution, take 25 mL and place it in a 50 mL stoppered conical flask, weigh 1.0 g of the resin adsorbent prepared in Example 1 (dry weight, the wet state can be converted into dry weight or directly weigh the adsorbent after constant weight by atmospheric pressure drying method) and put it into the flask, place it in a reciprocating constant temperature water bath oscillator at (37±1)°C and oscillate at a rate of (60±10) times / min for 2 h, measure and calculate the creatinine solution concentration before and after adsorption by ultraviolet spectrophotometry at 232 nm, and calculate the decline rate according to formula (3):

[0050]

[0051] Where:

[0052] c r3 ——Decrease rate of creatinine solution, %;

[0053] c 03 ——Concentration of creatinine solution before adsorption, in milligrams per liter (mg / L);

[0054] c t3 ——Concentration of creatinine solution after 2 hours of adsorption, in milligrams per liter (mg / L);

[0055] 4. Adsorption performance of sodium pentobarbital

[0056] Prepare an aqueous solution of sodium pentobarbital at a concentration of 80 mg / L, take 25 mL and place it in a 50 mL conical flask with a stopper, weigh 1.0 g of adsorbent (dry weight, wet state can be converted to dry weight or directly weigh the adsorbent after constant weight by atmospheric pressure drying method) and put it into the flask, place it in a reciprocating constant temperature water bath oscillator at (37±1)℃ and oscillate at a rate of (60±10) times / min for 2 hours, measure and calculate the concentration of sodium pentobarbital solution before and after adsorption by ultraviolet spectrophotometry at 240 nm, and calculate the decline rate according to formula (4):

[0057]

[0058] Where:

[0059] c r4 ——Decline rate of sodium pentobarbital solution, %;

[0060] c 04 ——Concentration of sodium pentobarbital solution before adsorption, in milligrams per liter (mg / L);

[0061] c t4 ——Concentration of sodium pentobarbital solution after 2 hours of adsorption, in milligrams per liter (mg / L); 5. Adsorption performance of VB12

[0062] Prepare a 25 mg / L VB12 aqueous solution, take 25 mL and place it in a 50 mL stoppered conical flask, weigh 1.0 g of the resin adsorbent prepared in Example 1 (dry weight, the wet state can be converted into dry weight or directly weigh the adsorbent after constant weight by atmospheric pressure drying method) and put it into the flask, place it in a reciprocating constant temperature water bath oscillator at (37±1)°C and oscillate at a rate of (60±10) times / min for 2 h, measure and calculate the VB12 solution concentration before and after adsorption by ultraviolet spectrophotometry at 361 nm, and calculate the decline rate according to formula (5):

[0063]

[0064] Where:

[0065] c r5 ——VB12 solution decline rate, %;

[0066] c 05 ——VB12 solution concentration before adsorption, in milligrams per liter (mg / L);

[0067] c t5 ——VB12 solution concentration after 2 hours of adsorption, in milligrams per liter (mg / L);

[0068] 6. Adsorption performance of lysozyme

[0069] Prepare a 400 mg / L lysozyme solution, take 25 mL and place it in a 50 mL stoppered conical flask, weigh 1.0 g of adsorbent (dry weight, wet state can be converted to dry weight or directly weigh the adsorbent after constant weight by atmospheric pressure drying method) and put it into the flask, place it in a reciprocating constant temperature water bath oscillator at (37±1)℃ and oscillate at a rate of (60±10) times / min for 2 h, measure and calculate the lysozyme solution concentration before and after adsorption by ultraviolet spectrophotometry at 281 nm, and calculate the decline rate according to formula (6):

[0070]

[0071] Where:

[0072] c r6 ——Lysozyme solution decline rate, %;

[0073] c 06 ——Concentration of lysozyme solution before adsorption, in milligrams per liter (mg / L);

[0074] c t6 ——Concentration of lysozyme solution after 2 hours of adsorption, in milligrams per liter (mg / L);

[0075] Test results:

[0076] Serial number Adsorbed substances Concentration before adsorption Concentration after 2h adsorption Adsorption rate (%) 1 Indoxyl sulfate 25mg / L 0.35mg / L 98.6 2 p-Cresol Sulfate 25mg / L 0.225mg / L 99.1 3 Creatinine 35mg / L 0.175mg / L 99.5 4 Sodium Pentobarbital 80mg / L 1.04mg / L 98.7 5 VB12 25mg / L 0.175mg / L 99.3 6 Lysozyme 400mg / L 6.8mg / L 98.3

[0077] Hemolytic performance test:

[0078] 1. Add 0.9% sodium chloride injection according to the condition of resin volume: extract volume = 1:1, and extract at 37℃ 60r / min for 72 hours.

[0079] 2. Test sample: 10 ml extract; negative: 10 ml 0.9% sodium chloride injection; positive: 10 ml purified water, 3 parallel tubes in each group; 37°C water bath for 30 min; add 0.2 ml rabbit blood to each tube (the preparation method of rabbit blood for the experiment is: take 8 ml rabbit blood, add 10 ml 0.9% sodium chloride injection, dilute and mix.), continue at 37°C for 60 minutes, and turn upside down twice every 30 minutes.

[0080] 3. Centrifuge and take the supernatant to detect the absorbance at 545 nm.

[0081] 4. Acceptance criteria: According to the provisions of YY / T 165-2019 "Hemolysis Test for Medical Devices Part 1: Material-mediated Hemolysis Test", the hemolysis rate shall be ≤5%.

[0082] 5. Test results

[0083] Style Name Style 1 Style 2 Style 3 Average absorbance Positive 0.7612 0.7395 0.7190 0.7399 Negative 0.0158 0.0150 0.0168 0.0159 Test product 0.0160 0.0212 0.0182 0.0185

[0084] Hemolysis rate: [(0.0185-0.0159) / (0.7399-0.0159)] = 0.359%

[0085] Example 2

[0086] (1) Preparation of aqueous phase: Add 1000 ml of water to a 2000 ml three-necked flask and heat to 45°C. Add 10 g of gelatin, 16 g of polyvinyl alcohol, 20 g of magnesium sulfate, 55 g of sodium carbonate, and 6 drops of methylene blue. Stir for 20 min until gelatin and polyvinyl alcohol are completely dissolved. Continue stirring for half an hour as the aqueous phase.

[0087] (2) Preparation of oil phase: Add 5 g of divinylbenzene (95%), 60 g of methyl methacrylate, 47 g of styrene, 35 g of toluene, 150 g of isobutyl alcohol, 0.5 g of BPO and 0.5 g of azo into a beaker and stir evenly. If necessary, ultrasonically mix to obtain the oil phase.

[0088] (3) Polymerization: Slowly add the oil phase to the water phase, start stirring and control the speed to 120r / min until the stirring is constant, and stir at a constant speed for 10 minutes. Raise the temperature from 45°C to 78°C at a rate of 5°C / 15min. After the resin is fixed for 3 hours, continue to raise the temperature to 85°C at a rate of 5°C / 10min, keep it warm for 2 hours, continue to raise the temperature from 85°C to 95°C at a rate of 5°C / 10min, keep it warm for 6 hours and then take it out. Wash the polyvinyl alcohol on the surface of the resin with warm water, extract the porogen with acetone in a Soxhlet extractor for 8 hours, wash with water and dry it to obtain white ball resin.

[0089] White ball indicators:

[0090]

[0091] (4) Acidic hydrolysis: Take 20g of dry white ball resin, add 100ml of purified water into a three-necked flask, add 50g of 5% sulfuric acid solution, stir for 2h, heat to 90-95℃ at a rate of 5℃ / 10min for hydrolysis, soak in 10% sulfuric acid solution for 2h, and wash with purified water for 1h. (At this time, the ester group in the resin forms a carboxyl group under the condition of sulfuric acid solution. A resin containing carboxyl groups is obtained).

[0092] Resin index:

[0093]

[0094] (5) Ethylene glycol condensation crosslinking: 20g of the dried resin after hydrolysis was added to a three-necked flask, and 80g of ethylene glycol was added to swell for 3h. During the swelling process, the temperature in the autoclave was controlled not to exceed 15°C. After the swelling was completed, 0.5% sulfuric acid solution was added dropwise and mixed evenly to make the pH value of the system <1, and then the temperature was raised to 75°C for reaction for 12h.

[0095] Condensation cross-linking resin indicators:

[0096]

[0097] Example 3

[0098] (1) Preparation of aqueous phase: Add 1000 ml of water to a 2000 ml three-necked flask and heat to 45°C. Add 15 g of gelatin, 20 g of polyvinyl alcohol, 20 g of magnesium sulfate, 58 g of sodium carbonate, and 7 drops of methylene blue. Stir for 20 min until gelatin and polyvinyl alcohol are completely dissolved. Continue stirring for half an hour as the aqueous phase.

[0099] (2) Preparation of oil phase: Add 4 g of divinylbenzene (95%), 40 g of methyl methacrylate, 43 g of styrene, 45 g of toluene, 200 g of isobutyl alcohol, 1 g of BPO and 0.5 g of azo into a beaker and stir evenly. If necessary, ultrasonically mix to obtain the oil phase.

[0100] (3) Polymerization: Slowly add the oil phase to the water phase, start stirring and control the speed to 120r / min until the stirring is constant, and stir at a constant speed for 10 minutes. Raise the temperature from 45°C to 78°C at a rate of 5°C / 15min. After the resin is fixed for 3 hours, continue to raise the temperature to 85°C at a rate of 5°C / 10min, keep it warm for 2 hours, continue to raise the temperature from 85°C to 95°C at a rate of 5°C / 10min, keep it warm for 6 hours and then take it out. Wash the polyvinyl alcohol on the surface of the resin with warm water, extract the porogen with acetone in a Soxhlet extractor for 8 hours, wash with water and dry it to obtain white ball resin.

[0101] White ball indicators:

[0102]

[0103] (4) Acidic hydrolysis: Take 20g of dry white ball resin, add 100ml of purified water into a three-necked flask, add 50g of 5% sulfuric acid solution, stir for 2h, heat to 90-95℃ at a rate of 5℃ / 10min for hydrolysis, soak in 10% sulfuric acid solution for 2h, and wash with purified water for 1h. (At this time, the ester group in the resin forms a carboxyl group under the condition of sulfuric acid solution. A resin containing carboxyl groups is obtained).

[0104] Resin index:

[0105]

[0106] (5) Ethylene glycol condensation crosslinking: 20g of the dried resin after hydrolysis was added to a three-necked flask, and 120g of ethylene glycol was added to swell for 3h. During the swelling process, the temperature in the autoclave was controlled not to exceed 15°C. After the swelling was completed, 0.5% sulfuric acid solution was added dropwise and mixed evenly to make the pH value of the system <1, and then the temperature was raised to 75°C for reaction for 12h.

[0107] Condensation cross-linking resin indicators:

[0108]

Claims

1. A method for synthesizing an ethylene glycol condensation cross-linked acrylic resin, characterized in that: The following steps are involved: Prepare the aqueous phase: add water, gelatin, polyvinyl alcohol, magnesium sulfate, sodium carbonate and methylene blue into a reaction container, heat and stir until gelatin and polyvinyl alcohol are completely dissolved, and continue stirring for half an hour as the aqueous phase; Preparation of oil phase: Add divinylbenzene, methyl methacrylate, styrene, toluene, isobutyl alcohol, BPO and azobisisobutyronitrile into a reaction container and mix well as the oil phase; Polymerization: slowly add the oil phase into the water phase, control the stirring speed to 120r / min until the stirring is constant, continue to stir at a constant speed for 10min, heat up to 78℃ at a rate of 5℃ / 15min, and continue to heat up to 85℃ at a rate of 5℃ / 10min after the resin is fixed for 3h, keep warm for 2h, continue to heat up to 95℃ at a rate of 5℃ / 10min, keep warm for 6h and then take out; Wash away the polyvinyl alcohol on the resin surface with warm water, extract the porogen with acetone using a Soxhlet extractor, and wash and dry to obtain the white ball resin; Acid hydrolysis: Add the white ball resin into the reactor, add 5% sulfuric acid solution into the reactor to cover the resin, stir to allow the sulfuric acid to fully enter the resin, and heat to 90-95℃ at a rate of 5℃ / 10min for hydrolysis; after the hydrolysis is completed, soak it in 10% sulfuric acid solution to dissolve the organic and inorganic substances in the resin, and wash off the excess sulfuric acid with pure water to obtain a resin containing carboxyl groups; Ethylene glycol condensation crosslinking: dry the carboxyl resin obtained in the previous step and add it into the reactor. Add ethylene glycol into the reactor to fully swell it. During the swelling process, control the temperature in the reactor not to exceed 15°C. After the swelling is completed, add 0.5% sulfuric acid solution dropwise and mix evenly to make the pH of the system less than 1. Raise the temperature to 75°C for full reaction.

2. The method for synthesizing the ethylene glycol condensation cross-linked acrylic resin according to claim 1, characterized in that: In the aqueous phase, add 10-15 g gelatin, 16-20 g polyvinyl alcohol, 16-20 g magnesium sulfate, 55-58 g sodium carbonate, and 6-7 drops of methylene blue per liter of water.

3. The method for synthesizing the ethylene glycol condensation cross-linked acrylic resin according to claim 1, characterized in that: The mass ratio of divinylbenzene, methyl methacrylate, styrene, toluene, isobutyl alcohol, BPO and azobisisobutyronitrile in the oil phase is 8-10:80-120:85-95:70-90:300-400:1-2:

1.

4. The method for synthesizing the ethylene glycol condensation cross-linked acrylic resin according to claim 1, characterized in that: In step (3), the mass ratio of the water phase to the oil phase is 2-4:

1.

5. The method for synthesizing the ethylene glycol condensation cross-linked acrylic resin according to claim 1, characterized in that: In step (5), 4-6 g of ethylene glycol is added per gram of resin containing hydroxyl groups.